Contribution to the knowledge of the genus Nephelomilta Hampson, 1900(Lepidoptera, Erebidae, Arctiinae) from China with descriptions of two new species - Huang, Si-Yao; Volynkin, Anton V.; Xiong, Yun; Li, Ying-Chun; Saldaitis, Aidas; Li, Xian-Fu (Zootaxa, 2023)
New information on the genus Nephelomilta Hampson, 1900 from China is reported. Two new species are described from southwestern China: N. medogensis Huang, Volynkin & Saldaitis, sp. n. from Motuo County, Xizang Autonomous Region and N. nu Huang, Volynkin & Saldaitis, sp. n. from Nujiang Valley, Yunnan Province. The female of N. yasunorikishidai Huang & Wang, 2019 is discovered and illustrated for the first time, and the species is erected into a separate species-group. Adults and genitalia of the aforementioned taxa and related ones as well are illustrated.